2015
DOI: 10.1007/s00134-015-3994-8
|View full text |Cite
|
Sign up to set email alerts
|

High-flow oxygen therapy in cancer patients with acute respiratory failure

Abstract: Electronic supplementary materialThe online version of this article (doi:10.1007/s00134-015-3994-8) contains supplementary material, which is available to authorized users.Dear Editor, Acute respiratory failure is a dramatic event and remains a major cause of ICU admission in cancer patients [1]. It has been recently shown that highflow oxygen therapy through a nasal cannula in association with noninvasive ventilation (HFNC-NIV) during acute respiratory failure is associated with high mortality in unselected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 5 publications
(8 reference statements)
4
49
0
2
Order By: Relevance
“…58,73,74 The use of high flow oxygen therapy through a nasal cannula (HFNC) associated with NIV recently demonstrated promising results in ARF in cancer patients, with a significant improvement of day-28 mortality and decrease in invasive MV requirement. 75 NIV appears to be highly effective in well-selected situations, such as cardiac edema and capillary leak syndrome, but totally ineffective in lesional pulmonary edema. This strategy deserves to be investigated in allo-HSCT patients.…”
Section: Prognostic Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…58,73,74 The use of high flow oxygen therapy through a nasal cannula (HFNC) associated with NIV recently demonstrated promising results in ARF in cancer patients, with a significant improvement of day-28 mortality and decrease in invasive MV requirement. 75 NIV appears to be highly effective in well-selected situations, such as cardiac edema and capillary leak syndrome, but totally ineffective in lesional pulmonary edema. This strategy deserves to be investigated in allo-HSCT patients.…”
Section: Prognostic Factorsmentioning
confidence: 97%
“…In the setting of cancer patients with hypoxemic ARF, HFNC associated with NIV was independently associated with improved survival and lower ventilation-free days. 75 The optimal oxygen delivery system is currently under examination, and a recent publication focused on Venturi mask versus HFNC in ARF immunocompromised patients, with no difference highlighted. 104 …”
Section: Icu Management Improvementsmentioning
confidence: 99%
“…In another study including patients with cancer and ARF, NHF in combination with NIV was associated with a lower 28-day mortality rate compared to either NHF alone or to a combination of SOT with NIV [71]. These results contrast with the results of the FLORALI (Clinical Effect of the Association of Non-invasive Ventilation and High Flow Nasal Oxygen Therapy in Resuscitation of Patients with Acute Lung Injury) study [26], in which the combination of NHF-NIV in an unselected population with hypoxaemic ARF was associated with high mortality.…”
Section: Acute Hypoxaemic Respiratory Failure In Immunocompromised Pamentioning
confidence: 96%
“…These results contrast with the results of the FLORALI (Clinical Effect of the Association of Non-invasive Ventilation and High Flow Nasal Oxygen Therapy in Resuscitation of Patients with Acute Lung Injury) study [26], in which the combination of NHF-NIV in an unselected population with hypoxaemic ARF was associated with high mortality. It is possible that the differences in the NIV application protocol (time and number of sessions) as well as the different study populations could explain the dissimilar results between studies [26,71]. The beneficial effects of NHF have been highlighted in two further studies in patients with solid tumours [72] and haematologic malignancies [73], where more than one-third of the patients improved while on NHF and another large percentage (44%) remained stable [72], often obviating the need for ICU admission or invasive mechanical ventilation.…”
Section: Acute Hypoxaemic Respiratory Failure In Immunocompromised Pamentioning
confidence: 99%
“…In critically ill cancer patients at high risk of mortality, there is an urgent need for additional data. In a retrospective cohort study matched and adjusted for potential confounders, Mokart et al found patients receiving both non-invasive ventilation (NIV) and high-flow nasal cannula oxygen therapy (HFNC) to have a lower mortality and more days free from invasive mechanical ventilation at day 28 [9]. This study should be taken cautiously as regard to unmeasured confounders that may have participated in treatment choice, but it does underline the need to perform trials specifically dedicated to this population [7][8][9].…”
Section: Treatmentsmentioning
confidence: 99%